(untitled) (TEL Tempo, Espaço e Linguagem, 2024)
This article aims to analyze the architecture of the body as a policy of heteronormativity and corponormativity. This is a theoretical research that uses studies by Anita Ghai (2002) and Ana Pereira (2007) to problematize the extent to which Article 12 of the principles in Paul Preciado Contrasexual Manifesto (2017) allows creating intelligibility to include the issue of people with disabilities at the heart of contrasexuality. The dildo, as a prosthesis that precedes the penis, becomes an extension of the body. The meanings constructed about body and power must be denaturalized to guarantee citizenship through social recognition, redistribution and political representation of women, transsexuals and people with disabilities. Keywords: Speaking Bodies. Political Control. Stigmatization